Factors influencing employee retention at Sense Services Sdn Bhd / Syafikah Aisyah Sulaiman - Sulaiman, Syafikah Aisyah (Faculty of Business and Management, 2018)
The employee retention is a continuous issues that most of the companies facing with. It is not easy to retain employees for a long period in the organization. The purpose of this study is to identify the factors that influence employee retention at Sense Services Sdn Bhd. It is very essential for the company to reduce employee turnover which may influence the organization`s productivity. Researcher has listed three variables which are working environment, supervisor support, and training and development as independent variables while employee retention as dependent variable.